An Uneasy Pleasure: Representing the Dangers of Skin-to-skin Contact in Eighteenth-century London ‘The William Bynum Prize Essay’ - Fernandes, Sara (Med Hist, 2019)
This article considers the social function of contagious disease as moderator of class relationships in England during the first half of the eighteenth century and takes into account the ways in which the ‘communicability’ of the plague, great pox (syphilis) and smallpox (variola) was used by authors to crystallise social interaction and tension along class lines. The essay begins by examining the representation of the plague, syphilis and smallpox in the medical tradition, before shifting its attention to the practice of maritime quarantine, as laid out by Richard Mead in his Short Discourse Concerning Pestilential Contagion (1720). By foregrounding medical writing on contagion through skin contact, I suggest that pornographic texts such as John Cleland’s The Memoirs of a Woman of Pleasure (Fanny Hill) (1748) had an interventionist function. Cleland is often charged with sanitising the true horrors of sex work in this period. This article proposes that if we take the time to appreciate the way infectious cutaneous diseases were believed to operate and spread we can recognise the moments in which he not only alludes to disease but invokes it for structural and thematic purposes. In proposing this, I am challenging the dominant interpretation that the problematic realities of eighteenth-century prostitution, especially disease, are subordinated to the narrative’s greater interest in erotic pleasure.